The taxonomic status of Palearctic and Nearctic populations of northern goshawk Accipiter gentilis (Aves, Accipitridae): New evidence from vocalisations - Sangster, George (Senckenberg Gesellschaft für Naturforschung, 2022)
The taxonomic status of the North American and Eurasian populations of northern goshawk A. gentilis has been called into question by recent molecular studies, indicating the need for additional taxonomic study. Vocalisations have long played an important role in diagnosing potentially reproductively isolated groups of birds. The chattering-type call of A. gentilis plays a role in advertisement and pair-contact, making this a suitable basis for taxonomic study of vocalisations. The data set consisted of recordings of the calls of 75 individuals of the Eurasian gentilis-group of A. gentilis, 37 of the North American atricapillus-group of A. gentilis and, for comparison, seven of Henst's goshawk A. henstii. The three groups showed non-overlapping variation in the duration of call-notes and also showed several other highly significant differences. Discriminant Function Analysis resulted in 100% correct classification of recordings into the three groups. It is here argued that the new bioacoustic data, in combination with previous evidence of morphological, mitochondrial DNA and genomic DNA differences between Eurasian and North American A. gentilis, suggests that two species are best recognised: northern goshawk A. gentilis and American goshawk A. atricapillus. A. gentilis / A. atricapillus add to a growing list of Holarctic temperate zone taxa that have recently been recognised as separate species based on a deep phylogeographic split between Eurasian and North American populations in combination with differences in other characters. This is the first quantitative taxonomic study of vocalisations in Accipitridae.